Exact Strategies to Increase Indonesian’s Millenial Customer Loyalty towards Digital Banking Product - Johan Hendri Prasetyo; Joko Ariawan (Institute of Computer Science (IOCS), 2022)
The appearence of digital and millennial disruption in Indonesia has been affected to banking competition particularly at digital banking. This forced the banks should implement various right strategies to keep customers out of this competition. This research aims to revealed the right strategy to increase millennial customer loyalty towards digital banking through service quality and perceived ease of use, likewise to customer satisfaction as an intervene. This research included in causality type with descriptive quantitative method processed by SEM-LISREL to examined the hypothesis. The sample was 400 respondents spread throughout Indonesia. The technique used non-probability sampling with snowball type. Research found that service satisfaction and perceived ease of use affects the increasing in millennial customer loyalty either directly or indirectly. Customer satisfaction has direct affect to increase customer loyalty. Service satisfaction and perceived ease of use affects in achieving millennial's expectation. Appropriate strategy to use to improve customer loyalty based on this research is by develop digital banking services that worthy and irreplaceable to reached sustained competitive advantage and creates algorithms learning machine to accommodate banking information in one mobile application which is reliable and convenient.